2D/3D covalent organic frameworks based on cobalt corroles for CO binding. (March 2023) - Yang, J.; André, L.; Desbois, N.; Gros, C.P.; Brandès, S.
Abstract: In the present work, the synthesis, characterization, and gas adsorption properties of new 2D covalent organic framework (COF) (2D-COF-Cor ) and 3D COF (3D-COF-Cor ) based on corrole macrocycles are reported. The two COFs have been synthesized by Schiff base condensation from readily available C 3 -symmetric aldehyde or T d -symmetric aldehyde as platforms, and diamine-functionalized free-base corrole as building block linker, to access 2D and 3D polymers, respectively. Cobalt-metalated COFs were also synthesized using a post-metalation procedure to give 2D-COF-CorCo and 3D-COF-CorCo as porous materials. The design of the 2D and 3D structures of the materials are reported, as well as the relationship between their structure and their performances for carbon monoxide (CO) adsorption. Spectroscopy analyses such as 1 H NMR, Fourier-Transform InfraRed (FTIR), powder X-ray diffraction, microscopic analyses, and sorption measurements were used to fully characterize the structure and the porosity of the COF materials. Their properties for capture and sensing of CO were also studied with the analysis of their isotherms using a multisite Langmuir isotherm model and the Ideal Adsorbed Solution Theory (IAST) theory. The affinity, capacity and selectivity of these materials for CO sorption were calculated. Compared to 3D-COF-CorCo, 2D-COF-CorCo reveals the highest adsorption capacity of 32.2 cm 3 /g for CO (298 K, 1 atm) with a high selectivity over N2, O2, CO2, up to 50, 130, 5090, 3170, respectively. In addition, FTIR analysis gave clear evidence of the involved solid–gas interactions, and the reversibility of CO binding on the cobalt metal center of the corrole within the materials. These results point out an appealing way of using cobalt corrole-based COF as efficient chemosensors to detect trace amounts of CO. Graphical abstract: Image 1 Highlights: Use of cobalt corrole-based COFs as efficient chemosensors for detecting trace amounts of CO. Synthesis, characterization, and gas adsorption properties of new 2D and 3D COF porous materials based on corrole macrocycles. Possible acute detection and poison prevention of CO thanks to cobalt corrole coordination.